Development of a dendritic cell‐targeting lipopeptide as an immunoadjuvant that inhibits tumor growth without inducing local inflammation. Issue 12 (14th May 2014) - Akazawa, Takashi; Ohashi, Toshimitsu; Nakajima, Hiroko; Nishizawa, Yasuko; Kodama, Ken; Sugiura, Kikuya; Inaba, Toshio; Inoue, Norimitsu
<x xml:space="preserve">Abstract</x> Materials used for the past 30 years as immunoadjuvants induce suboptimal antitumor immune responses and often cause undesirable local inflammation. Some bacterial lipopeptides that act as Toll‐like receptor (TLR) 2 ligands activate immune cells as immunoadjuvants and induce antitumor effects. Here, we developed a new dendritic cell (DC)‐targeting lipopeptide, h11c (P2C‐ATPEDNGRSFS), which uses the CD11c‐binding sequence of intracellular adhesion molecule‐1 to selectively and efficiently activate DCs but not other immune cells. Although the h11c lipopeptide activated DCs similarly to an artificial lipopeptide, P2C‐SKKKK (P2CSK4), via TLR2 in vitro, h11c induced more effective tumor inhibition than P2CSK4 at low doses in vivo with tumor antigens. Even without tumor antigens, h11c lipopeptide significantly inhibited tumor growth and induced tumor‐specific cytotoxic T cells. P2CSK4 was retained subcutaneously at the vaccination site and induced severe local inflammation in in vivo experiments. In contrast, h11c was not retained at the vaccination site and was transported into the tumor within 24 hr. The recruitment of DCs into the tumor was induced by h11c more effectively, while P2CSK4 induced the accumulation of neutrophils leading to severe inflammation at the vaccination site. Because CD11b+ cells, but not CD11c+ cells, produced neutrophil chemotactic factors such as macrophage inflammatory protein (MIP)‐2 in response to stimulation with TLR2 ligands, the DC‐targeting lipopeptide h11c induced less MIP‐2 production by splenocytes than P2CSK4. In this study, we succeeded in developing a novel immunoadjuvant, h11c, which effectively induces antitumor activity without adverse effects such as local inflammation via the selective activation of DCs.